2014
DOI: 10.1002/2013jc009493
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an oceanic anticyclone in the lee of Madeira Island: In situ and remote sensing survey

Abstract: Island wakes are areas of a strong eddy activity influencing the availability and transport of organic matter in the ocean which, in turn impact biological productivity. Despite this, eddy formation in the lee of North Atlantic tropical islands is scarcely documented, except for the Canary Islands. Moreover, the occurrence of anticyclones leeward of Madeira has seldom been detected. During the summer of 2011, a multiplatform approach, combining satellite data with in situ measurements, was used to study an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 65 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…Such autonomous systems, although deployed from a research vessel, are not tethered to the vessel and operate without direct human control while collecting data (Yoerger et al, 1998(Yoerger et al, , 2007Griffiths, 2003). Therefore, they enable data acquisition in parts of the ocean such as beneath ice sheets in polar regions previously inaccessible to vessel-based sampling methods (Bellingham et al, 2000;Brierley et al, 2002;Nicholls et al, 2006;Wadhams et al, 2006;Dowdeswell et al, 2008;Jenkins et al, 2010;Graham et al, 2013), and are improving spatial and temporal resolution of undersea measurements (Niewiadomska et al, 2008;Caldeira et al, 2014). They also provide transformative opportunities to fisheries scientists and oceanographers to study marine population and ecosystem dynamics (Fernandes et al, 2003;Ohman et al, 2013).…”
Section: Marine Autonomous Systemsmentioning
confidence: 99%
“…Such autonomous systems, although deployed from a research vessel, are not tethered to the vessel and operate without direct human control while collecting data (Yoerger et al, 1998(Yoerger et al, , 2007Griffiths, 2003). Therefore, they enable data acquisition in parts of the ocean such as beneath ice sheets in polar regions previously inaccessible to vessel-based sampling methods (Bellingham et al, 2000;Brierley et al, 2002;Nicholls et al, 2006;Wadhams et al, 2006;Dowdeswell et al, 2008;Jenkins et al, 2010;Graham et al, 2013), and are improving spatial and temporal resolution of undersea measurements (Niewiadomska et al, 2008;Caldeira et al, 2014). They also provide transformative opportunities to fisheries scientists and oceanographers to study marine population and ecosystem dynamics (Fernandes et al, 2003;Ohman et al, 2013).…”
Section: Marine Autonomous Systemsmentioning
confidence: 99%
“…Recently, Molemaker et al (2015) and Gula et al (2015) have showed the linkages among boundary current separation, instability, and subsequent formation of anticyclones, as a result of current-topography interaction. Wind-wake can also generate eddy in the lee of island (Couvelard et al 2012;Caldeira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale eddies can be formed through vertical mixing (due to air-sea-ice interactions or induced by rough topography, major current barotropic/baroclinic instabilities and/or detachments from the boundary circulation due to the continental slope curvature (Caldeira et al, 2014) and/or other effects like upwelling (Bosse et al, 2015). Mesoscale eddies can be classified according to their formation mechanism because they present similar characteristics and core properties.…”
Section: Mesoscale and Submesoscale Phenomenamentioning
confidence: 99%